A resource allocation method of the product−service process based on process mining - Zhou, Xuequan; Liu, Yuqi; Zacharewicz, Gregory; Zhang, Hua; Chen, David (Frontiers in Manufacturing Technology, 2022)
With the evolution of product service system, as well as the proposal and wide application of cloud computing and big service, more and more manufacturing enterprises are turning from product-oriented to service-oriented. A difficult aspect is that with the growth of customer scale and the personalization of customer service needs, service providers cannot rely on their own resources to fulfill services. Moreover, meeting needs of customers often requires a complete and complex service. Therefore, the service provider has to provide cross enterprise collaborative services and coordinate the resources of all participants in the product service system to complete the services together. This research proposes a novel resource allocation method for product service system that adopts Bilateral Resource Integration Service mode and considers the service process life cycle. Based on the process mining techniques, this method extracts knowledge from the execution event log of the service process stored in the enterprise information system, constructs the resource allocation problem model, and gives the process mining based resource allocation algorithm (PMRA). Its pilot application in an air conditioner repair service case. The contribution of this study is to propose a new method of resource allocation for cross-enterprise product service processes based on process mining techniques, which takes into account empirical knowledge from historical data and can provide a new idea for service optimization of product service system.